Holding on to the MDGs (For Now) - Wickstead, M. R. (2012)
As we move into 2010, this article argues that there are three questions to ask in the MDGs review. First, have MDGs maintained their political resonance? Second, are the MDGs still realistic? Third, are the MDGs still an adequate proxy for the complexities of development? It considers some of the capacity constraints to progress in Africa, and the range of inputs required to reach desired outcomes - the MDGs.